Neuropathological characterization of the cavitating leukoencephalopathy caused by COA8 cytochrome c oxidase deficiency: a case report - Chapleau, Alexandra; Boucher, Renée-Myriam; Pastinen, Tomi; Thiffault, Isabelle; Gould, Peter V.; Bernard, Geneviève (Frontiers in Cellular Neuroscience, 2023)
COA8-related leukoencephalopathy is a recently described rare cavitating leukoencephalopathy caused by biallelic variants in the COA8 gene. Clinically, it presents heterogeneously and usually follows a bi-phasic clinical course with a period of acute onset and regression, followed by stabilization, and in some cases, even subtle improvement. We present a 4-year-old boy with a homozygous 2.5 kilobase pair deletion in the COA8 gene following a severe neurological deterioration resulting in death weeks after onset. Brain MRI revealed a distinctive pattern of cavitating leukodystrophy predominantly involving the posterior cerebral white matter which improved upon a follow-up MRI a month later. Brain pathology displayed overall white matter destruction with gliosis and infiltration by macrophages. There was preservation of astrocytes around blood vessels and axons around the zones of demyelination. This study is the first neuropathological examination of COA8-related leukoencephalopathy and provides further characterization of the clinical and MRI phenotype.